POLR3A and POLR3B Mutations in Unclassified Hypomyelination - Cayami, Ferdy K.; La Piana, Roberta; van Spaendonk, Rosalina M. L.; Nickel, Miriam; Bley, Annette; Guerrero, Kether; Tran, Luan T.; van der Knaap, Marjo S.; Bernard, Geneviève; Wolf, Nicole I. (Neuropediatrics, 2015)
Objective This study aims to ascertain frequency of mutations in POLR3A or POLR3B, which are associated with 4H leukodystrophy, in a cohort of patients with unclassified hypomyelination.Methods and Results In a cohort of 22 patients with the magnetic resonance imaging (MRI) diagnosis of unclassified hypomyelination and without typical clinical signs, we evaluated clinical and MRI features. Developmental delay or intellectual disability, ataxia, and spasticity were frequent symptoms. POLR3A and POLR3B were sequenced. A compound heterozygote mutation in POLR3B was found in only one patient. Additional investigations allowed a definitive diagnosis in 10 patients.Conclusion Mutations in POLR3A or POLR3B are rare in patients with unclassified hypomyelination, and alternative diagnoses should be considered first.
Keywords: hypomyelination; MRI; 4H syndrome; POLR3A; POLR3B